2020
DOI: 10.1186/s40545-020-0202-1
|View full text |Cite
|
Sign up to set email alerts
|

Advertisement of antibiotics for upper respiratory infections and equity in access to treatment: a cross-sectional study in Nepal

Abstract: Background: Pharmaceutical companies actively advertise their branded antibiotics, which influence their sales at community pharmacies. The major proportion of out of pocket health spending is on medicine; and affordability of antibiotics has always been a crucial issue in most developing countries. This study identified promotional activities adopted by pharmaceutical companies in community pharmacies and medicine shops and the affordability of selected antibiotics to clients with lowest wages in Kavrepalanch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…However, studies that examined financial incentives found a positive association with prescribing. [ 104,153 ] The fact that pharmaceutical companies have extensive marketing practices indicates per se that they believe that such campaigns are effective for shaping physician attitudes, and ultimately their own sales. [ 154 ]…”
Section: Factors Driving Variation In Antibiotic Use and Overusementioning
confidence: 99%
“…However, studies that examined financial incentives found a positive association with prescribing. [ 104,153 ] The fact that pharmaceutical companies have extensive marketing practices indicates per se that they believe that such campaigns are effective for shaping physician attitudes, and ultimately their own sales. [ 154 ]…”
Section: Factors Driving Variation In Antibiotic Use and Overusementioning
confidence: 99%
“…Acute upper respiratory infections (ARTIs) are considered to be the most common diagnosis for prescription of antimicrobials [11]. As viruses are the most common etiological agents, ARTIs are also associated with an increased burden of inappropriate antimicrobials use and subsequent AMR [11,12]. In our study, 68% of pharmacy respondents replied that respiratory infections were the most common complaints for patients requesting antimicrobials, followed by urinary and gastrointestinal infections.…”
Section: Discussionmentioning
confidence: 83%
“…Further, azithromycin was also ranked as the first most commonly sold antimicrobials in our study, followed by amoxicillin and cefixime. Koju et al reported that amoxicillin, azithromycin, amoxi-clavulanate, cefixime, and ciprofloxacin were the top five most commercially promoted antimicrobials for ARTIs in the community pharmacies of Nepal, which could have a direct influence on an increased prescription and sell of these antimicrobials [12]. Another study from Nepal found that cefixime (38%), amoxicillin (29.3%), ciprofloxacin (13.7%), and azithromycin (8.1%) were the most commonly dispensed antimicrobials by community pharmacies [13].…”
Section: Discussionmentioning
confidence: 99%
“…The frequent use of cephalosporins in Japan may be due in part to the active promotion of these antimicrobials by pharmaceutical companies. A study conducted in Nepal showed that the top-selling antimicrobials were those that were subjected to intensive promotional activities [21]. Although such promotional activities have since diminished in Japan, the situation was similar to that of Nepal as recently as 10 years ago.…”
Section: Discussionmentioning
confidence: 97%